Resposta aguda do sistema nervoso autônomo a diferentes estímulos auditivos musicais em mulheres - Ferreira, Lucas Lima [UNESP]; Vanderlei, Luiz Carlos Marques [UNESP]; Valenti, Vitor Engrácia [UNESP] (Universidade Federal de Sao Paulo, 2015)
Objective. To compare the acute response of the autonomic nervous system (ANS) before exposure to auditory stimuli of different musical styles in women. Method. Cross-sectional study with 27 women aged between 18 and 30 years old, apparently healthy. Volunteers remained at rest for 10 minutes and were exposed to classical music (64-84 dB) and heavy metal (75-84 dB) for 10 minutes, via headset, and their heart rate variability (HRV) was recorded during the entire period. Statistical indices were analyzed in the time domain and indexes in the frequency domain: low frequency component (LF), high frequency (HF) and LF/HF ratio of HRV. Results. There was an increase in the LF index (p=0.04) and decrease in HF index (p=0.02) in comparing stimuli of heavy metal and classical music. There was also a difference in LF/HF ratio (p=0.007) when comparing classical and heavy metal music. Conclusion. The acute response to exposure of the SNA musical auditory stimuli through headphones attended incremental component of the sympathetic, parasympathetic withdrawal and increased sympathetic-vagal balance component in heavy metal style compared to classical music.
Acute response of the autonomic nervous system to different musical auditory stimuli in women
Keywords: Autonomic nervous system; Cardiovascular System; Music